A review of the roles of pathogens in Alzheimer’s disease - Zhao, Meng; Wang, Yongchun; Shen, Yanxin; Wei, Chunxiao; Zhang, Guimei; Sun, Li (Frontiers in Neuroscience, 2024)
Alzheimer’s disease (AD) is one of the leading causes of dementia and is characterized by memory loss, mental and behavioral abnormalities, and impaired ability to perform daily activities. Even as a global disease that threatens human health, effective treatments to slow the progression of AD have not been found, despite intensive research and significant investment. In recent years, the role of infections in the etiology of AD has sparked intense debate. Pathogens invade the central nervous system through a damaged blood–brain barrier or nerve trunk and disrupt the neuronal structure and function as well as homeostasis of the brain microenvironment through a series of molecular biological events. In this review, we summarize the various pathogens involved in AD pathology, discuss potential interactions between pathogens and AD, and provide an overview of the promising future of anti-pathogenic therapies for AD.